A Concept for Application of Hall Sensors in Measurement of Magnetic Field over Magnetic Catapult Tracks - Sławomir CZUBAJ; Anna SIBILSKA-MROZIEWICZ; Edyta ŁADYŻYŃSKA-KOZDRAŚ (Problemy Mechatroniki, 2019)
The growing demand for commercial unmanned aerial vehicles (UAV) requires that innovative technical solutions for the critical aspects of UAV servicing, must be researched. The magnetic catapult discussed in this work is an interesting alternative to the existing UAV deployment or launch platforms. This paper presents the research designed to facilitate the measurement and analysis of the position of a launch truck applied in a UAV magnetic catapult with tracks. The measurement system discussed herein comprised a transducer connected to Hall sensors which were spaced evenly at the base of a superconductor pod. A displacement of the superconductor pod relative to the magnetic field resulted in the variation of the voltage output from individual Hall sensors. A proprietary algorithm was developed and controlled stepper motors which displaced the assembly of the superconductor pod with the Hall sensors along the test track of the UAV magnetic catapult. At the same time as the displacement was sensed by the Hall sensors, they were reading the real-time magnetic strength; it was therefore critical for the microcontroller, which executed the control algorithm, to operate at a sufficient processing frequency (speed). The proprietary control algorithm was executed by an ATMEL ATmega2560 RISC processor. The processor system read the status of every Hall sensor in the assembly and compared it to the reference voltage outputs stored in the microcontroller’s memory. The difference between the voltage output reading and the reference voltage outputs and the superconductor pod’s geometry was used to determine the superconductor pod’s position along the magnetic tracks of the UAV magnetic catapult.